Internationalization of Higher Education: Lithuanian Experience in Bologna Process and Beyond - Vaiva Zuzeviciute; Birute Praneviciene; Zaneta Simanaviciene; Violeta Vasiliauskiene (Montenegrin Journal of Economics, 2017)
The purpose of the article is to investigate the influence of international documents on the process of internationalization of higher education and to identify political, legal, organizational, financial pre-requisites for internationalization of higher education in Lithuania. Method of comparative critical analysis of references was employed for the study.